The Role of Indonesian Notaries in the Transfer of Intellectual Property Rights - Tansari, Noviana (International Journal of Social Service and Research, 2025)
The transfer of Intellectual Property Rights (IPR) in Indonesia necessitates legal certainty and protection, roles fulfilled by notaries through authentic deeds. This study examines the strategic functions of notaries in IPR transfers, focusing on their roles as proof providers, trusted third parties, and compliance keepers. Using normative legal research with a regulatory approach, the study analyzes laws such as the Copyright Law, Patent Law, and Trademark Law, alongside secondary data from document studies. Findings reveal that notarial deeds serve as irrefutable evidence in IPR transfers, ensuring compliance with legal standards and reducing dispute risks. Notaries also facilitate transparency in digital IPR registrations, enhancing trust among parties. The research highlights the notary’s obligation to verify IPR statuses and ensure transactional validity under Article 1320 of the Civil Code. Implications suggest that notaries are pivotal in safeguarding economic rights and adapting to technological advancements in IPR management. This study contributes to the literature by delineating the notary’s expanded role in contemporary IPR transactions, offering insights for policymakers and legal practitioners to strengthen IPR frameworks.